Hydrogen Permeation in PEM Electrolyzer Cells Operated at Asymmetric Pressure Conditions. Issue 11 (1st January 2016) - Trinke, P.; Bensmann, B.; Reichstein, S.; Hanke-Rauschenbach, R.; Sundmacher, K.
Abstract : The present contribution investigates the hydrogen permeation through a fumea EF-40 catalyst coated membrane during PEM water electrolysis. The permeation is characterized at different temperatures and different pressure gradients across the membrane. The measured permeation fluxes show a quadratic dependence on the pressure difference. A permeation model combining a diffusive and convective transport can describe the experimental data quantitatively. The determined diffusive permeability coefficient K P, diff eff = 2.95 × 10 − 14 mol/(m s Pa) at 60 °C and its temperature dependence agrees very well with literature values. A convective permeability coefficient of the membrane is proposed for the description of the quadratic dependence. The obtained convective permeability coefficient K P, conv eff = 9.02 × 10 − 21 mol/(m s Pa 2 ) at 60 °C indicates a high hydraulic permeability in comparison with recently reported values. This high hydraulic permeability can be attributed especially to the low equivalent weight of the investigated membrane. Additionally, the operating conditions are suspected to support permeation.